Daseinsvorsorge in Gefahr: öffentliche Bibliothekenzwischen Digitalisierung und Austerität. - Thiele, Katja (Copernicus Publications, 2020)
Public libraries are an important public service of general interest and, as part of social infrastructures, contribute to educational justice. This article discusses their development against the background of the interaction of digitization and austerity. As voluntary services they are particularly affected by the current austerity policy and have to increasingly justify their services and structures. At the same time, they are being rediscovered in the course of local authorities' urban development strategies. Based on empirical results from Bonn, the paper discusses central municipal strategies for the further development of the local library system and sheds light on the associated ambivalent socio-spatial implications.
Keywords: Öffentliche Bibliothek; Daseinsvorsorge; Bildungseinrichtung; Teilhabe; Kulturangebot; Digitalisierung; Stadtentwicklungsplanung; Bibliotheksbau; Kommunale Dienstleistung; Sozialinfrstruktur